Employees’ Attitude towards Psychological Contract in Selected Industries - Kaushal, Neelam; Ghalawat, Suman; Malik, Joginder Singh; Singh, Ajit; Kumari, Neelam (Indian Journal of Extension Education, 2020)
Psychological contract, defined as genuine but unrecorded opportunities of employees or the personnel regarding the employer plays a crucial role. Psychological Contract (PC) displays the obligations, rewards, prospective rights etc. that an employee believe is due by the employer in exchange for the employment or job and loyalty of employees. The Psychological Contract is a vital feature of place of work relationships and the comparatively wider behavior of human. The study examines feelings and opinions of employees regarding psychological contract. A survey was conducted to collect data from 245 employees of five different industries (Telecom, IT, Education, Retail and Banking). To analyse data, statistical software SPSS 19 was used. The findings revealed that age, experience, industry and salary all contributed to affect psychological contract of the employees. Regarding psychological contract gender was not found to be significant, hence the organization need to take special care in this regard. The paper concludes with a discussion of the implications of employee’s PC for educational research and practice.
Keywords: Psychological Contract; Contract breach; Industry; ANOVA